2019
DOI: 10.1080/10717544.2019.1682720
|View full text |Cite
|
Sign up to set email alerts
|

Eprinomectin nanoemulgel for transdermal delivery against endoparasites and ectoparasites: preparation, in vitro and in vivo evaluation

Abstract: Nanoemulgels are composed of O/W nanoemulsion and hydrogels and are considered as ideal carriers for the transdermal drug delivery because these have high affinity to load hydrophobic drugs. The stable formulation of eprinomectin (EPR) is very challenging because of it is high hydrophobic nature. In this work, we have prepared EPR loaded nanoemulgel for the treatment of endo-and ectoparasites. The surface morphology of optimized formulations was characterized by scanning electron microscopy. Additionally, skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 36 publications
(38 reference statements)
1
25
0
Order By: Relevance
“…The area supplied with the tested formulation was observed for 3 days and no irritation, edema or erythema was detected during the entire period of study. The results are in accordance with Mao et al, who observed no irritation on skin treated with eprinomectin nanoemulgel [20].…”
Section: Skin Irritation Studysupporting
confidence: 92%
See 1 more Smart Citation
“…The area supplied with the tested formulation was observed for 3 days and no irritation, edema or erythema was detected during the entire period of study. The results are in accordance with Mao et al, who observed no irritation on skin treated with eprinomectin nanoemulgel [20].…”
Section: Skin Irritation Studysupporting
confidence: 92%
“…A nanoemulgel is a novel preparation for transdermal delivery that forms as a result of incorporating a nanoemulsion within a hydrogel, which provides the formulation with dual characteristics. It has the ability to deliver hydrophobic drugs, which is considered a great challenge that can limit the drug application [ 20 ]. Hydrophobic drugs could be entrapped in the oily phase of the nanoemulsion and then the droplets of the nanoemulsion are incorporated into the gel preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The in situ gelling nanoemulgel of naringin was tested for biocompatibility in the L929 mouse fibroblast cell line (National Centre for Cell Sciences, NCCS, Pune, India) [ 31 ]. The cells were maintained in DMEM and distributed in 96-well plates (1 × 10 4 cells per well) for 24 h in a 5% CO 2 atmosphere at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The in situ gelling nanoemulgel of naringin was tested for biocompatibility in the L929 mouse fibroblast cell line (National Centre for Cell Sciences, NCCS, Pune, India) [31]. The cells were maintained in DMEM and distributed in 96-well plates (1 × 10 4 cells per well) for 24 h in a 5% CO 2 atmosphere at 37 • C. After this period, the medium was removed and the adhered cells were treated with formulations (4 dilutions taking 0.2 g/mL of formulation in DMEM as 100% and further dilution with DMEM to obtain 50%, 25% and 12.5%, n = 6) under the same incubation conditions.…”
Section: Biocompatibility and Toxicity Analysis 281 In Vitro Testing For Biocompatibility With L929 Cell Linementioning
confidence: 99%
“…Nanoemulgel is a nanoemulsion that contains a gelling ingredient [13]. According to various experimental findings regarding emulgel dosage forms, a drug from nanoemulgel can permeate the skin via both transcellular and paracellular routes, whereas nanoemulsion only delivers the drug via the transcellular route [14,15].…”
Section: Introductionmentioning
confidence: 99%